2023
DOI: 10.1136/rmdopen-2023-003196
|View full text |Cite
|
Sign up to set email alerts
|

What is the best target in a treat-to-target strategy in rheumatoid arthritis? Results from a systematic review and meta-regression analysis

Abstract: ObjectivesA treat-to-target (T2T) strategy has been shown to be superior to usual care in rheumatoid arthritis (RA), but the optimal target remains unknown. Targets are based on a disease activity measure (eg, Disease Activity Score-28 (DAS28), Simplified Disease Activity Indices/Clinical Disease Activity Indices (SDAI/CDAI), and a cut-off such as remission or low disease activity (LDA). Our aim was to compare the effect of different targets on clinical and radiographic outcomes.MethodsCochrane, Embase and (pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 96 publications
0
4
0
Order By: Relevance
“…This knowledge gap highlights the need for updated education on recent advances in RA diagnosis, emphasizing the importance of early diagnosis and treatment to achieve remission in early RA and low disease activity in established cases. 27 A significant knowledge deficit was also observed in the investigation and treatment of RA. More than half of the respondents were unaware of the classification criteria for RA, and a similar proportion did not know that the rheumatoid factor is not definitive for diagnosis, believing that RA can be diagnosed without serology tests.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This knowledge gap highlights the need for updated education on recent advances in RA diagnosis, emphasizing the importance of early diagnosis and treatment to achieve remission in early RA and low disease activity in established cases. 27 A significant knowledge deficit was also observed in the investigation and treatment of RA. More than half of the respondents were unaware of the classification criteria for RA, and a similar proportion did not know that the rheumatoid factor is not definitive for diagnosis, believing that RA can be diagnosed without serology tests.…”
Section: Discussionmentioning
confidence: 98%
“…It is concerning that 9 out of 10 family physicians believe that RA is characterized by joint deformities, indicating that RA may not be considered until deformities develop. This knowledge gap highlights the need for updated education on recent advances in RA diagnosis, emphasizing the importance of early diagnosis and treatment to achieve remission in early RA and low disease activity in established cases 27 …”
Section: Discussionmentioning
confidence: 99%
“…Patients in remission typically require fewer healthcare resources, including medications, hospitalizations, and surgeries [ 26 ]. This reduction in healthcare utilization not only lowers healthcare costs but also allows patients to return to work and daily activities, contributing to their economic well-being [ 27 ].…”
Section: Reviewmentioning
confidence: 99%
“…Clinical remission is widely accepted as the main therapeutic target in RA, with low disease activity (LDA) as a viable alternative in patients who are unable to achieve remission. As a result of the complexity of the disease, patients with RA may require multiple trials of medications with different mechanisms of action (MoAs) to achieve their treatment goal [ 3 6 ]. However, despite the number of currently approved advanced therapies with different MoAs available for patients with RA, including bDMARDs, multiple clinical trials and post-marketing reports [ 2 , 7 10 ] have shown that a minority of patients achieve remission or LDA when assessed using the Clinical Disease Activity Index (CDAI) or the Simplified Disease Activity Index, metrics favored by the American College of Rheumatology (ACR) and European Alliance of Associations for Rheumatology (EULAR) for assessing disease activity in RA [ 3 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%